Microbiological diagnosis of pulmonary invasive aspergillosis in critically ill patients with severe SARS-CoV-2 pneumonia: a bronchoalveolar study - Ángel Estella; Ignacio Martín-Loeches; María Recuerda Núñez; Clara González García; Liliana Marcela Pesaresi; Alvaro Antón Escors; Maria Dolores López Prieto; Juan Manuel Sánchez Calvo (BMC, 2023)
Abstract Background Diagnosing COVID-19-associated pulmonary aspergillosis (CAPA) can be challenging since radiological and clinical criteria in the critically ill patient are nonspecific. Microbiological diagnostic support is therefore crucial. The aim of this study was to document the incidence of aspergillosis using bronchoalveolar lavage (BAL) as the diagnostic method and to determine the performance of the current mycological diagnostic tests most widely used for the diagnosis of CAPA, together with evaluation of the Asp lateral flow device (LFD). Methods Prospective cohort study conducted between March 2020 and June 2022. Inclusion criteria were critically ill patients admitted to the ICU with SARS-CoV-2 pneumonia requiring invasive mechanical ventilation. Diagnostic bronchoscopy and BAL were performed at the beginning of invasive mechanical ventilation. The sensitivity, specificity, positive and negative predictive value (PPV and NPV), positive and negative likelihood ratio (LR + and LR-) of BAL culture, direct examination with calcofluor white stain, ELISA (Platelia) and LFD (AspLFD) for detection of galactomannan (GM) were evaluated. Aspergillus-qPCR was applied when discrepancies between diagnostic tests arose. Results Of the 244 critically ill patients with SARS-CoV-2 pneumonia admitted to the ICU, the majority (n = 200, 82%) required invasive mechanical ventilation. Diagnostic bronchoscopic procedures were performed in 160 patients (80%), who were enrolled in this study. The incidence of CAPA was 18.7% (n = 30). LFD-GM demonstrated a sensitivity of 84%, specificity of 99%, PPV 94%, NPV 97%, LR(+) of 84, and LR(-) of 0.16. At GM-ELISA indices of ≥ 0.5 and ≥ 1.0, sensitivity was 92% and 79%, specificity was 95% and 99%, PPV 76% and 91%, NPV 99% and 96%, LR(+) 18 and 79, and LR(-) 0.08 and 0.21, respectively. The optimal cut-off index from the ROC curve was 0.48, with sensitivity of 95% and specificity of 95%. Conclusions Using a diagnostic strategy based on bronchoscopy and BAL, we documented a high incidence of pulmonary aspergillosis in patients with severe SARS-CoV-2 pneumonia. Asp-LFD showed moderate sensitivity and excellent specificity, with a high PPV, and could be used for rapid diagnosis of patients with suspected CAPA.